2016
DOI: 10.1152/ajpregu.00227.2014
|View full text |Cite
|
Sign up to set email alerts
|

Complex reinnervation pattern after unilateral renal denervation in rats

Abstract: Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…In the present study, these were unlikely cofounders as we used a standard surgical–pharmacological approach for extensive RDNx and showed that renal tissue norepinephrine levels at the end of the study were at an accepted level of suppression (<90% of control animals) for interruption of functional responses. Furthermore, and consistent with our findings, morphological evidence of nerve regrowth is not accompanied by an increase of renal norepinephrine content in rats, at least until 12 weeks post-denervation, well beyond the timeframe of our study ( Rodionova et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, these were unlikely cofounders as we used a standard surgical–pharmacological approach for extensive RDNx and showed that renal tissue norepinephrine levels at the end of the study were at an accepted level of suppression (<90% of control animals) for interruption of functional responses. Furthermore, and consistent with our findings, morphological evidence of nerve regrowth is not accompanied by an increase of renal norepinephrine content in rats, at least until 12 weeks post-denervation, well beyond the timeframe of our study ( Rodionova et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…A close relationship of SP-positive nerve fibers to afferent and efferent arterioles and glomeruli was already described more than three decades ago [47]. We could confirm this finding with respect to SP [13,48]. However, such an interaction must not necessarily occur in the kidney since peptides like SP could be secreted along the whole surface of the axon and not only at the nerve endings [58].…”
Section: Sp Involvement In Renal Innervationsupporting
confidence: 79%
“…Renal denervation reduced concentrations of SP in the respective kidneys to hardly detectable levels 7 days after the procedure pointing to neurogenic sources of SP [ 48 ]. Interestingly, the cellular distribution of the primary receptor for SP in the kidney has so far not raised too much attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In normotensive rats, reinnervation of the afferent renal sensory nerves and the efferent renal sympathetic nerves occurs over the same time course, both being complete at 9–12 weeks after RD. 35 Similarly, report of Booth et al 36 showed the reinnervation of renal afferent and efferent nerves at 5.5 months after catheter-based radiofrequency renal denervation in sheep and by 11 months the functional afferent and efferent responses to electric stimulation were normal.…”
Section: Discussionmentioning
confidence: 85%